Cell-type-specific expression of the rat thyroperoxidase promoter indicates common mechanisms for thyroid-specific gene expression. - Francis-Lang, H (1992)
A 420-bp fragment from the 5' end of the rat thyroperoxidase (TPO) gene was fused to a luciferase reporter and shown to direct cell-type-specific expression when transfected into rat thyroid FRTL-5 cells. Analysis of this DNA fragment revealed four regions of the promoter which interact with DNA-binding proteins present in FRTL-5 cells. Mutation of the DNA sequence within any of these regions reduced TPO promoter activity. The trans-acting factors binding to these sequences were compared with thyroid transcription factor 1 (TTF-1) and TTF-2, previously identified as transcriptional activators of another thyroid-specific gene, the thyroglobulin (Tg) gene. Purified TTF-1 binds to three regions of TPO which are protected by FRTL-5 proteins. Two of the binding sites overlap with recognition sites for other DNA-binding proteins. One TTF-1 site can also bind a protein (UFB) present in the nuclei of both expressing and nonexpressing cells. TTF-1 binding to the proximal region overlaps with that for a novel protein present in FRTL-5 cells which can also recognize the promoter-proximal region of Tg. Using a combination of techniques, the factor binding to the fourth TPO promoter site was shown to be TTF-2. We conclude, therefore, that the FRTL-5-specific expression of two thyroid restricted genes, encoding TPO and Tg, relies on a combination of the same trans-acting factors present in thyroid cells.